Asuhan Keperawatan Keluarga pada Ny. S dengan Gangguan Sistem Kardiovaskular : Hipertensi di Desa Kalibuntu RT 02 RW 03 Kecamatan Losari Kabupaten Brebes - Satya Rizaldi Alamsyah; Siti Fatimah; Sujono Sujono (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Hypertension is still one of the problems that exist in the community today. Ordinary people know hypertension as high blood pressure because this disease has a high increase in blood pressure outside normal limits (Marbun and Hutapea 2022). The purpose of this writing is to be able to make and apply Family Nursing Care to Mrs S with Cardiovascular System Disorders: Hypertension in Kalibuntu Village Rt 02 Rw 03 Losari District, Brebes Regency. This writing method uses a descriptive method with a nursing process approach study. The results of nursing care Clients often feel dizzy and headache, the back of the head feels heavy. Pain in the nape of the neck. Pain increases during activity and decreases when resting. Pain like being cut into pieces. Pain in the nape of the neck. Pain scale 4 (moderate pain). Pain is intermittent. The client said he knew about hypertension, but did not know in detail about what causes hypertension, signs and symptoms of hypertension, and how to prevent and treat complaints. The nursing diagnoses raised are acute pain and knowledge deficit. Interventions are carried out based on SIKI and implementation based on interventions that have been designed. In the evaluation of the two diagnoses there is one resolved diagnosis, namely knowledge deficit, partially resolved diagnoses, namely acute pain. The results of nursing care have no gaps with theory. Writing i